The multiple directions of antiferromagnetic spintronics - Jungwirth, Tomas; Sinova, Jairo; Manchon, Aurelien; Marti, Xavier; Wunderlich, J.; Felser, Claudia (Nature Physics, 2018)
New developments in spintronics based on antiferromagnetic materials show promise for improved fundamental understanding and applications in technology.
CRIS-Team Scopus Importer:2022-04-14